Methodology for the Development of Radar Control Systems for Flying Targets with an Artificially Reduced RCS - Igor Parkhomey; Juliy Boiko; Oleksander Eromenko (Journal of Robotics and Control (JRC), 2022)
The article explores methods for detecting and tracking air targets in radar with an artificially reduced radar cross-section (RCS). A technique for control the radar antenna system using an adaptive method is presented, which is based on adapting the system to the conditions of information uncertainty due to fluctuations in the excitation signal of the radar target's radar-absorbing coating. Known methods of radar aircraft (active and passive, which do not take into account the structure of the coating of the aircraft) do not allow obtaining information about an air target with an artificially reduced RCS. The main contribution of this article is the development of radar and control methods based on the resonant frequency-phase interaction of the microwave electromagnetic field with the crystal structure of the radar absorbing coating of the aircraft. The stages of antenna system control based on the "frequency-phase detection method", "passive-active" tracking method, and "adaptive method" of antenna control have been studied. To test the proposed methods, an experiment was conducted to determine the transient process in the control system under conditions of information uncertainty. As a result of the experiment, the probability of tracking the target is increased by 14-19%. The findings will be useful for developers of radar and control systems for modern air facilities with an artificially reduced RCS.